Hubungan Tingkat Pengetahuan Ibu Tentang Toilet Training Terhadap Pelaksanaan Toilet Training Pada Anak Usia Toddler Di Kelurahan Sewu Surakarta - Putri, Anggita Kesuma, Siti Arifah, S.Kep., M.Kes (2016)
The toddler who was at the age of 12 to 36 months is a period of intensive exploration of the environment as a child trying to find out how it all happened, in this period is an important period to achieve the development and growth of children. Parents have an important role in optimizing the development of children, provide stimulation in all aspects of the development of both gross motor and fine motor, language, social and personal. One aspect common development in the toddler period is teaching to the toilet, 18 months of age children are able to withstand the bladder. Knowledge of toilet training is very important to be owned by a parent, especially a mother, good knowledge means having a good understanding in optimizing every stage of development, one of which implementation toilet training in children ages toddler. The purpose of the study to determine the relations of mother knowledge level about toilet training to implementation of toilet training at toddler in Sub Sewu. This type of research is quantitative with cross sectional method. Techniques of data collection used questionnaires. Respondents in this research were 44 mothers who has children ages toddler by simple random sampling. The statistical analysis used was Spearman Rank. The results of this study the level of knowledge of mothers in both categories by 55% and the implementation of toilet training in children ages toddler in both categories as much as 57%. There was a significant relations of mother knowledge level about toilet training to implementation of toilet training on toddler in Sub Sewu in getting test results Rank Spearman ρ-value 0.590 to 0.001. Suggestions for further research is to be a reference to develop more extensive research on the methods and other factors Keywords : knowledge, toilet training, toddler Consist of fifty-two literature from 2006-2016